2020
DOI: 10.18585/inabj.v12i4.1315
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis in Health and Disease: Molecular Mechanisms

Abstract: BACKGROUND: Hormesis was initially defined as a phenomenon where a small dose of harmful agent exposure to living organisms gives beneficial effects. The dose and time of this ‘tress’ exposure has become the object of investigation across the broad range of biomedical studies.CONTENT: Hormesis characterized by the biphasic dose-effect or time-effect relationship for any substance. Some hormetic mechanisms performed biological plasticity, involve oxidative damage which instead induce antioxidant enzyme producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 157 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…The increase in cell viability at lower concentrations can be due to the hormetic effect. It can be observed as either a xenobiotic or an antioxidant substance, a hormone or a metabolite in several studies [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in cell viability at lower concentrations can be due to the hormetic effect. It can be observed as either a xenobiotic or an antioxidant substance, a hormone or a metabolite in several studies [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…did not have cytotoxic effects on Caco-2 cells. Furthermore, several studies on fish-based protein hydrolysates on multiple human cell lines have shown low toxicity and high cell viability [ 51 , 52 ]. Gómez et al [ 56 ] showed a cytoprotective effect after 24 h of treatment with red tilapia side streams in Caco-2 cells, demonstrating an increase in cell viability in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…These play critical roles in scavenging free radicals and reducing oxidative damage, thus demonstrating the hermetic effects that promote cellular resilience and longevity [38,39]. This exercise intensity also triggers the NRF2 signaling pathway, a vital regulator of cellular antioxidant mechanisms, thereby boosting the body's ability to mitigate oxidative stress and protect against cardiovascular and metabolic disorders [25,52,57,60]. Conversely, high-intensity exercise can lead to an overload of reactive oxygen and nitrogen species, overwhelming the antioxidant defense and resulting in cellular damage, muscle fatigue, and impaired recovery, conditions often exacerbated during continuous intense training without adequate rest [26,40,66].…”
Section: Modulation Of Oxidative Stress Through Exercise Intensitymentioning
confidence: 99%
“…While direct antioxidant supplementation has shown limited efficacy and potential risks, strategies to induce mild oxidative stress like hormesis could improve the body's natural defense mechanisms and increase sensitivity to cancer treatments [37]. Key transcription factors, NF-κB and Nrf2, regulate the expression of antioxidant enzymes, demonstrating how low-level stress can enhance health and longevity by triggering protective responses against various stressors [60]. Additionally, the body's adaptation to environmental, physical, and nutritional stress through hormesis involves epigenetic changes, highlighting the importance of understanding these responses for health and longevity.…”
Section: Introduction To the Concept Of Hormesis Within The Context O...mentioning
confidence: 99%
“…Hormesis is defined by a biphasic dose-response relationship where low-dose exposures elicit stimulatory effects, while high-dose exposures produce inhibitory outcomes. 1 This adaptive response serves to facilitate acclimation, thereby enhancing an organism's resilience, which can be beneficial. One such instance is the physiological hormetic responses induced by low-level exposure to hypoxia, enhancing the performance of the organism.…”
Section: Introductionmentioning
confidence: 99%